Women’s Experience of Sexual Harassment in Carpet Factories - Dhakal, G (Journal of Nepal Health Research Council, 2010)
Background: Sexual harassment is a problematic issue where women and men work together. It is being recognized as a violation of human rights and human dignity which undermines the equality of opportunity and treatment between men and women. So, this study was conducted in Kathmandu which helps to find out women's experience of sexual harassment and its impact on them. Methods: Descriptive study was conducted in six carpet factories, selected purposively. A semi-structured questionnaire was used to find out experience of sexual harassment and its impact on their job, mental and physical health. The organizational context and job context of those factories were also studied. Results: From the study, 72% workers had heard about Sexual Harassment and among them, 52% had faced it in their workplace. The most frequent type of sexual harassment was passing vulgar jokes, remarks or teasing obscenely (87%). Twenty three percent of the workers felt disruption on their job, 61% were affected mentally and 8% were affected physically after harassment. All the workers felt provision and execution of penalty to the perpetrator. But none of the factory had policy on sexual harassment or none of the worker had complained about sexual harassment to the authority yet. Conclusions: Female workers are very much vulnerable to sexual harassment by their male co workers. It negatively impacts their performance, mental and physical health. There should be sexual harassment policy in their organization to maintain a fair and productive working environment and implementation is must. Key words: sexual harassment; working women; workplace; workers. DOI: 10.3126/jnhrc.v7i2.3015 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 98-102